Notas bibliográficas (1966)
A Second Course in Number Theory, COHN, J. Wiley, N.Y. /  Abelian Categories, P. Frero, Harper and amp; Row, N.Y. / Introduction a la Theorie des Categories, G. Postov, Offilib, Paris